Empire of the minds - Abd Razak, Dzulkifli (2007)
MALAYSIA held its first Higher Education Conference and Exhibition in Dubai, the United Arab Emirates, last week. The event was attended by potential students and highranking officials from the Middle East and the North Africa (Mena) region. As many as 15 Malaysian universities took part in support of the ministry's internationalisation effort. No doubt, this in tandem with the global trend where knowledge sharing is a vital component of higher education. As testimony to this, at a not too distant venue, a Knowledge Conference was opened by Shaikh Mohammed Rashid Al Maktoum, vicepresident and prime minister of the UAE and Ruler of Dubai.